Family Support for Postpartum Blues - Dewi, Adinda Putri Sari (Universitas Muhammadiyah Lamongan, 2022)
Background: As many as 50-70% of all postpartum women in Indonesia experience postpartum blues and this can lead to postpartum depression with varying amounts from 5% to more than 25%. Involving the family during the postpartum period is one of the efforts that can be made to prevent postpartum blues. This is because family support is a preventive strategy to reduce stress in postpartum mothers.Objectives: To find out the relation between family support and the incidence of postpartum blues in the Rahmah Room at PKU Muhammadiyah Gombong Hospital.Design: This research is a quantitative study with a correlational design with a cross sectional approach. The total population in this study were 200 postpartum mothers. Based on the large sample slovin formula, there were 133 respondents in this study. The sample collection method used is purposive sampling, which is a sampling technique by determining certain criteria. In analyzing data in a bivariate manner, data testing was carried out using the Kendal Tau correlation test with a significant level of 95%.Data Sources: primary data sources and data collection using family support questionnaires and EPDS measurement sheetsResults: The results showed that there was a relation between family support and the incidence of postpartum blues in the Rahmah Room at PKU Muhammadiyah Gombong Hospital with a p-value of 0.001 <0.05.Conclusions: There is a relation between husband's support and the incidence of postpartum blues in the Rahmah Room at PKU Muhammadiyah Gombong Hospital.